CTCF acetylation at lysine 20 is required for the early cardiac mesoderm differentiation of embryonic stem cells - Shixin Gong; Gongcheng Hu; Rong Guo; Jie Zhang; Yiqi Yang; Binrui Ji; Gang Li; Hongjie Yao (Cell Regeneration, 2022)
Abstract The CCCTC-binding factor (CTCF) protein and its modified forms regulate gene expression and genome organization. However, information on CTCF acetylation and its biological function is still lacking. Here, we show that CTCF can be acetylated at lysine 20 (CTCF-K20) by CREB-binding protein (CBP) and deacetylated by histone deacetylase 6 (HDAC6). CTCF-K20 is required for the CTCF interaction with CBP. A CTCF point mutation at lysine 20 had no effect on self-renewal but blocked the mesoderm differentiation of mouse embryonic stem cells (mESCs). The CTCF-K20 mutation reduced CTCF binding to the promoters and enhancers of genes associated with early cardiac mesoderm differentiation, resulting in diminished chromatin accessibility and decreased enhancer-promoter interactions, impairing gene expression. In summary, this study reveals the important roles of CTCF-K20 in regulating CTCF genomic functions and mESC differentiation into mesoderm.